2017
DOI: 10.1021/acsmedchemlett.7b00347
|View full text |Cite
|
Sign up to set email alerts
|

χ-Space Screening of Dermorphin-Based Tetrapeptides through Use of Constrained Arylazepinone and Quinolinone Scaffolds

Abstract: Herein, the synthesis of novel conformationally constrained amino acids, 4-amino-8-bromo-2-benzazepin-3-one (8-Br-Aba), 3-amino-3,4-dihydroquinolin-2-one, and regioisomeric 4-amino-naphthoazepinones (1- and 2-Ana), is described. Introduction of these constricted scaffolds into the -terminal tetrapeptide of dermorphin (i.e., H-Tyr-d-Ala-Phe-Gly-NH) induced significant shifts in binding affinity, selectivity, and in vitro activity at the μ- and δ-opioid receptors (MOP and DOP, respectively). A reported constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…First, methyl substitutions were introduced at the β-position of Phe13 to restrict rotations of its side chain in the χ space . Mono- or dimethyl substitutions on racemic Phe showed little effect on ligand binding profiles ( 23 , K i 0.37 nM; 24 , K i 0.36 nM vs Ape13, K i 0.7 nM), and no significant impact on signaling was observed.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…First, methyl substitutions were introduced at the β-position of Phe13 to restrict rotations of its side chain in the χ space . Mono- or dimethyl substitutions on racemic Phe showed little effect on ligand binding profiles ( 23 , K i 0.37 nM; 24 , K i 0.36 nM vs Ape13, K i 0.7 nM), and no significant impact on signaling was observed.…”
Section: Resultsmentioning
confidence: 66%
“…Dipeptides 11a and 11b were obtained after final ester hydrolysis. The synthesis of Fmoc-1-Ana-Gly-OH (not shown) was completely performed as described previously …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, when the aromatic moieties were turned towards the C-terminus of the peptide sequences, (partial) (ant)agonism at MOP and weak (ant)agonism at DOP were noticed, whereas the incorporation of the 1-Ana residue (with the aromatic moiety shifted towards the N-terminus) led towards balanced low nanomolar MOP/DOP binding and in vitro agonism. [1] Additionally, a 3-step methodology for the synthesis of 1,5-benzothiazepin-4(5H)-one dipeptidomimetics has been elaborated via an Ugi-4CR followed by a S-trityl deprotection and an intramolecular Cu(I)-catalyzed Ullmann condensation with moderate to good yields. In silico and NMR conformational studies showed that the lowest energy conformers stabilize γ-and β-turn structures.…”
Section: Introductionmentioning
confidence: 99%